2018
DOI: 10.3892/or.2018.6394
|View full text |Cite
|
Sign up to set email alerts
|

miR‑186 functions as a tumor suppressor in osteosarcoma cells by suppressing the malignant phenotype and aerobic glycolysis

Abstract: Osteosarcoma (OS) is the most common primary bone malignancy among children and adolescents. Deregulation of microRNAs has been well documented in OS, while the putative effects of miR‑186 have not been identified yet. In the present study, we assessed the expression of miR‑186 in a cohort of 40 OS tissues and explored its effects on OS cells. As expected, miR‑186 was suppressed in OS tissues compared with relative normal tissues. Overexpression of miR‑186 inhibited cell proliferation, arrested the cell cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…To further explore the mechanism of upstream signaling of Shp2, we predicted the targeting relationship between miR-186 and Shp2 through the website. It's reported that miR-186 inhibits the development of non-small lung cancer, colon cancer, cervical cancer and gastric cancer [27][28][29][30]. In our study, dual luciferase reporter assay confirmed that miR-186 negatively regulates Shp2 gene.…”
Section: Discussionsupporting
confidence: 78%
“…To further explore the mechanism of upstream signaling of Shp2, we predicted the targeting relationship between miR-186 and Shp2 through the website. It's reported that miR-186 inhibits the development of non-small lung cancer, colon cancer, cervical cancer and gastric cancer [27][28][29][30]. In our study, dual luciferase reporter assay confirmed that miR-186 negatively regulates Shp2 gene.…”
Section: Discussionsupporting
confidence: 78%
“…Osteosarcoma (OS) is a primary malignant tumor of the skeleton characterized by the direct formation of immature bone or osteoid tissue in the tumor cells. 1 More rarely, OS may arise in the soft tissue. About 75% of cases, patients with OS are between 15 and 25 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, miR-323a-3p results significantly downregulated in OS tissues and cell lines, while its overexpression reduces cell viability [150]. In addition, a different miRNA, namely miR-186, which decreases indirectly lactate levels through direct inhibition of HIF-1α and glycolysis, functions as a tumor suppressor of both HOS and U2 OS cell lines, inhibiting tumor cell proliferation and invasion [151].…”
Section: Lactate and Sarcomasmentioning
confidence: 73%